Supramodal neural networks support top‐down processing of social signals. Issue 3 (19th October 2020) - Sonderfeld, Melina; Mathiak, Klaus; Häring, Gianna S.; Schmidt, Sarah; Habel, Ute; Gur, Raquel; Klasen, Martin
Abstract: The perception of facial and vocal stimuli is driven by sensory input and cognitive top‐down influences. Important top‐down influences are attentional focus and supramodal social memory representations. The present study investigated the neural networks underlying these top‐down processes and their role in social stimulus classification. In a neuroimaging study with 45 healthy participants, we employed a social adaptation of the Implicit Association Test. Attentional focus was modified via the classification task, which compared two domains of social perception (emotion and gender), using the exactly same stimulus set. Supramodal memory representations were addressed via congruency of the target categories for the classification of auditory and visual social stimuli (voices and faces). Functional magnetic resonance imaging identified attention‐specific and supramodal networks. Emotion classification networks included bilateral anterior insula, pre‐supplementary motor area, and right inferior frontal gyrus. They were pure attention‐driven and independent from stimulus modality or congruency of the target concepts. No neural contribution of supramodal memory representations could be revealed for emotion classification. In contrast, gender classification relied on supramodal memory representations in rostral anterior cingulate and ventromedial prefrontal cortices. In summary, different domains of social perception involve different top‐down processes which take place in clearly distinguishable neural networks. Abstract : The perception of facial and vocal stimuli is driven by cognitive top‐down influences. In the present study, we identified specific neural networks for the contributions of attentional focus and supramodal memory, depending on the classification task.